An Analysis of The Balanced Lifestyle and Recreational Sports Practices of Foreign Students Enrolled in Graduate Programs According to Different Variables (The Case of Kütahya Province) - RADHİ, Yahya Jaber Radhi and YUKSEL, Oguzhan and GÜNDÜZ, Bolat (International Journal of Holistic Health, Sports and Recreation, 2025)
This study aims to examine the balanced living standards and recreational sports well-being of foreign students enrolled in graduate programs at Dumlupınar University according to demographic and socio-cultural variables. The sample of the study, conducted using a quantitative correlational survey design, consisted of a total of 399 students (116 female, 283 male) actively enrolled in master’s and doctoral programs. After ensuring normality, descriptive statistics, independent samples t-test, one-way ANOVA, Tukey post-hoc, and correlation analyses were applied; the significance level was set at p<.05. The findings showed that age created significant differences in the spirituality sub-dimension of balanced life and that recreational participation duration created significant differences in the physical sub-dimension; however, there were no differences in the success, physical, spirituality, and relationship dimensions based on marital status, gender, length of stay in Turkey, education and income status, participation status, and place of residence. In recreational sports well-being, a significant difference was found only in the physical-mental health sub-dimension according to the income variable. Correlations showed that the Total Balanced Life score was highly positively correlated with success, spirituality, and relationships; moderately positively correlated with body; and weakly positively correlated with life satisfaction, family relationship development, and positive emotions. The Recreational Sports Well-Being Total score was found to be highly positively correlated with life satisfaction, positive emotion, physical-mental health, and family relationship development; and low positively correlated with success, spirituality, body, and relationship. The results show that the two constructs are multidimensional and strongly correlated, particularly through subjective well-being components.